2016
DOI: 10.1021/acs.jpclett.6b01224
|View full text |Cite
|
Sign up to set email alerts
|

Dual Strong Couplings Between TPPS J-Aggregates and Aluminum Plasmonic States

Abstract: We report on the spectral properties of strong coupling between the localized surface plasmon resonances (LSPRs) of aluminum (Al) nanostructures and tetraphenylporphyrin tetrasulfonic acid hydrate (TPPS) J-aggregates. Because of their wide spectral range of LSPR bands from ultraviolet to near-infrared wavelengths by controlling structural size, Al nanodisks can realize strong coupling with different excitons of TPPS J-aggregates. The Rabi splitting energies of the excitons based on Soret and Q bands are 300 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
24
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 38 publications
5
24
0
Order By: Relevance
“…An error of about 20% has been estimated for this value because of the uncertainty in precisely selecting the position and the width of the experimental bands. Nevertheless, the estimated value is in good agreement with previous findings [46][47][48] and the strong coupling condition (specifically Ω R 2 > (γ exc 2 + γ pl 2 )/2) holds in any case.…”
Section: Extinction Spectrasupporting
confidence: 91%
See 1 more Smart Citation
“…An error of about 20% has been estimated for this value because of the uncertainty in precisely selecting the position and the width of the experimental bands. Nevertheless, the estimated value is in good agreement with previous findings [46][47][48] and the strong coupling condition (specifically Ω R 2 > (γ exc 2 + γ pl 2 )/2) holds in any case.…”
Section: Extinction Spectrasupporting
confidence: 91%
“…These bands present the typical anti-crossing behavior expected when plexcitonic resonances are formed upon the mixing of the plasmonic and excitonic resonances. Similar features were also reported for H 2 -TPPS 2− J-aggregates strongly coupled with Al nanodisks 46 and nanostructured silver films. 47,48 Therefore, these two bands can be attributed to the formation of an upper (UR) and a lower (LR) plexciton resonance, arising from the strong coupling between the 490 nm exciton resonance of H 2 -TPPS 2− J-aggregates and the plasmon resonance of NPs.…”
Section: Extinction Spectrasupporting
confidence: 85%
“…From a practical point of view, fabrication techniques to make nanoparticle arrays with excellent precision over large areas have made these systems reliable platforms for different experiments [48,49]. One of the emerging fields of research, in which arrays of metallic nanoparticles supporting SLRs have demonstrated their potential, is strong light-matter coupling [32,50,[51][52][53]. Strong light-matter coupling between optical modes in a cavity with quantum emitters is an interesting direction in the field of quantum optics with implications for nonlinear optics, photochemistry, charge transfer, and exciton transport.…”
Section: Introductionmentioning
confidence: 99%
“…Then, conical pit arrays with a period from 300 to 450 nm can be replicated on top of the Al film with a total area of 50 × 50 μm 2 . Al was selected not only simply for its costeffectiveness and abundance, but also for the wide SP spectral range (Li et al, 2016). Here, the processed Al nanopits with uniform size (as shown in Figure 1C) show a plasmon resonance that matches with the broad absorbance spectrum of CH 3 NH 3 PbCl x I 3-x film.…”
Section: Methodsmentioning
confidence: 99%